2018
DOI: 10.1186/s40246-018-0144-8
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of stakeholders in psychiatry towards the inclusion of children in genomic research

Abstract: BackgroundGenomic sequencing of children in research raises complex ethical issues. This study aims to gain more knowledge on the attitudes towards the inclusion of children as research subjects in genomic research and towards the disclosure of pertinent and incidental findings to the parents and the child.MethodsQualitative data were collected from interviews with a wide range of informants: experts engaged in genomic research, clinical geneticists, persons with mental disorders, relatives, and blood donors. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…Despite increasing consensus that some clinically relevant findings should be offered to individual participants in genomics research, 6,8,[16][17][18] including psychiatric genetics, 10,[19][20][21] there is little empirical data about how to ideally manage return of results (RoR) in the psychiatric genetics research context. 22,23 Most research on RoR in genetics research has focused on whether results should be offered, and the perceived risks and benefits of returning results, [7][8][9]18,24,25 along with which types of results (e.g., medically actionable, clinically valid but not actionable) are justifiable and recommended to return.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite increasing consensus that some clinically relevant findings should be offered to individual participants in genomics research, 6,8,[16][17][18] including psychiatric genetics, 10,[19][20][21] there is little empirical data about how to ideally manage return of results (RoR) in the psychiatric genetics research context. 22,23 Most research on RoR in genetics research has focused on whether results should be offered, and the perceived risks and benefits of returning results, [7][8][9]18,24,25 along with which types of results (e.g., medically actionable, clinically valid but not actionable) are justifiable and recommended to return.…”
Section: Introductionmentioning
confidence: 99%
“…7,10 While these studies have opened a broader dialogue about whether results should be offered and why, only a few empirical studies to date have specifically addressed which results should be offered and how results should be returned in psychiatric genetics research. [19][20][21]27 No empirical study has examined these issue from the perspective of psychiatric genomics researchers who are key stakeholders in implementing plans for returning results.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, Sundby et al () found that psychiatric genetics stakeholders (i.e., patients with mental health disorders, their relatives, and clinicians) favor the return of both pertinent (95%) and incidental (91%) findings to research participants (Sundby et al, ), including to parents of child participants and to the children themselves when of legal age (Sundby et al, ). In another study, 97% of patients with a psychiatric disorder and unaffected relatives reported that they would like to be informed of any clinically relevant genomic findings generated in a study (Bui, Anderson, Kassem, & McMahon, ).…”
Section: Introductionmentioning
confidence: 99%
“…Available guidelines recommend that predictive genetic testing should only be performed in minors if there is a potential direct medical benefit, or if preventive measures initiated in childhood will decrease morbidity and mortality (Committee on Bioethics, 2013; EURAT, ; European Society of Human Genetics, ). However, some experts question this approach, and suggest that it may be too narrow (Hardart & Chung, ; Sundby et al, ). The findings of some studies suggest that parents may be more reluctant to consent to genetic testing in their children following in‐depth discussion of the potential consequences (Bernhardt, Tambor, Fraser, Wissow, & Geller, ; Geller, Tambor, Bernhardt, Wissow, & Fraser, ).…”
Section: Discussionmentioning
confidence: 99%